Sleep duration and risk of incident stroke by age, sex, and race: The REGARDS study - Petrov, Megan E. (Neurology, 2018)
OBJECTIVE: To investigate the association between reported sleep duration and incident stroke in a US cohort of black and white adults, and evaluate race, age, and sex as potential effect modifiers. METHODS: From 2008 to 2010, 16,733 black and white adults, aged ≥45 years, without a history of stroke or sleep-disordered breathing from the Reasons for Geographic and Racial Differences in Stroke (REGARDS) study, reported their habitual sleep duration (<6, 6.0–6.9, 7.0–8.9 [reference], ≥9 hours). Incident strokes were identified through biannual participant contact followed by physician adjudication of medical records. Cox proportional hazards analysis was conducted to calculate hazard ratios of interactions between sleep duration with race, age, sex, and 2-way combinations of these factors on incident stroke adjusting for stroke risk factors and sleep-disordered breathing risk. RESULTS: The sample comprised 10.4% (n = 1,747) short sleepers (<6 hours) and 6.8% (n = 1,134) long sleepers (≥9 hours). Over an average 6.1 years follow-up, 460 strokes occurred. There were significant interactions between sleep duration and race (p = 0.018) and sleep duration and race–sex groups (p = 0.0023) in association with incident stroke. Short sleep duration was significantly associated with decreased risk for stroke among black participants (hazard ratio [HR] 0.49 [95% confidence interval (CI) 0.28–0.85]), particularly black men (HR 0.21 [95% CI 0.07–0.69]), whereas long sleep duration was significantly associated with increased risk for stroke among white men (HR 1.71 [95% CI 1.06–2.76]). CONCLUSIONS: The association of sleep duration with incident stroke differs by race and sex, with short sleep duration among black men associated with decreased risk, whereas long sleep duration among white men associated with increased risk for stroke.